Mengali Ibadah Bangsa Israel: Menyadari Kekurangan, Menyelaraskan Keadilan, dan Kebenaran dalam Amos 5:21-24 - Emanuel Filip Tungary; Bernardus Dirga Primawan (Sekolah Tinggi Teologi Jaffray Jakarta, 2023)
Worship in the tradition of the Israelite religion is an integral part of their lives. However, it should be realized that the worship conducted by the Israelites during that time was not yet perfect. Perfect worship goes beyond mere religious practices; it involves the application of virtuous values, especially justice and truth, which were being experienced by the impoverished society of that era. The statements of Amos give rise to two meanings regarding the establishment of justice for the poor or the justice upheld by the nation of Israel as a whole. Therefore, this research aims to delve deeper into the worship of the Israelite nation, highlight the deficiencies in its implementation, and find ways to align the values of justice and truth in that worship. This research adopts a literature study approach by examining the texts and historical contexts within the books of Amos in the Bible. The study reveals that the worship of the Israelite nation during that time tended to disregard the values of justice and truth being endured by the impoverished society. Ritualistic worship practices fail to reflect the application of virtuous values that should be an integral part of worship. Hence, efforts are needed to align the values of justice and truth in the practice of Israelite worship.